(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The article discusses preventive strategies for maxillary diseases including inflammatory, traumatic, degenerative, and neoplastic conditions. The importance of oral hygiene, elimination of infection foci, and comprehensive preventive programs is emphasized. Based on clinical observations and literature analysis, a preventive framework is proposed.